IMPLEMENTASI PERDA NO. 4 TAHUN 2008 TENTANG PENANGGULANGAN KEMISKINAN DI KOTA SEMARANG (BIDANG KESEHATAN, PENDIDIKAN DAN PENINGKATAN KETERAMPILAN) - sekar raras handayani; yuwanto .; ahmad taufiq (Journal of Politic and Government Studies, 2016)
Semarang has been well-known as the city with the highest poverty rate in Central Java, compared with the other cities from the same province. In order to solve that problem, in 2008, Semarang regional government had established its regulations, no. 4 of 2008 on handling the poverty. The purpose is to handle and solve the poverty rate in Semarang, which could be said as relatively higher than the other cities in Central Java. The problem in this research is about how the implementation of Semarang Regional Government Regulation No. 4 of 2008 and its barrier and enabler factors. This research’s purpose is to understand the implementation of Semarang Regional Government Regulation No. 4 of 2008, along with its barrier and enabler factors, in solving the poverty in Semarang.The method used on this research is descriptive qualitative method, focusing on the periods of 2010-2015 policies, as well as using George C. Edward’s theory regarding policy implementation. The data were taken from in-depth interview, photos, documents, and observations.The results of this research are as follows: Semarang Regional Government Regulation No. 4 of 2008 has been done by Specialized Team on Handling The Regional Poverty (TKPKD) which consisted of several SKPDs. BAPEDA has identified the poors for once per two years. Healthcare, education, and skill enhancement are extremely needed by the society. All programs in those three sectors had been done right on target based on the procedures. Healthcare programs had been implemented through Kartu Semarang Sehat, education programs through tuition free, and skill enhancement programs through training courses. The helps and services for the poor had been done properly.As a whole, the implementation of Semarang Regional Government Regulation No. 4 of 2008 did not give significant effects towards poverty in Semarang. The target, which is decreasing poverty by 2% per year, still could not be accomplished yet. For 5 years, Semarang regional government can only passed 6% of poverty rate, from 10% of its true goal.Therefore, Semarang Regional Government needs to prepare better implementation, as well as enhance its human resources by increasing the quality and the quantity of its officers.Keywords: Policy implementation, Poverty